2005
DOI: 10.1111/j.1439-0396.2005.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary ruminally protected l‐carnitine on plasma metabolites in sheep following a sub‐lethal ammonia challenge

Abstract: In Experiment 1, lambs were randomly assigned to 0.25, 1.00, 2.50, 5.00 and 10.00 g/day of dietary ruminally protected L-carnitine (RPLC) and were allowed to adapt for 20 days. Plasma samples were obtained at 0, 120 and 240 min after RPLC feeding. Plasma L-carnitine (LC) concentrations increased (p<0.01) for all levels of RPLC treatment, however, no differences were observed due to level of RPLC or time. Plasma LC concentrations were 27.05 and 57.83 micromol/l for baseline and pooled RPLC treated sheep, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…In this study, supplementation with unprotected and rumen-protected L-carnitine (the concentration of L-carnitine was 200 mg/kg basal diet) had no effect on plasma Lcarnitine concentration (P> 0.05; Table 6). Contrary to the results in this study, Walker et al (2005) reported that among different feeding dosages (0.125, 1.06, and 2.0 g/d),…”
Section: Plasma Biochemical Indices and L-carnitine Concentrationcontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, supplementation with unprotected and rumen-protected L-carnitine (the concentration of L-carnitine was 200 mg/kg basal diet) had no effect on plasma Lcarnitine concentration (P> 0.05; Table 6). Contrary to the results in this study, Walker et al (2005) reported that among different feeding dosages (0.125, 1.06, and 2.0 g/d),…”
Section: Plasma Biochemical Indices and L-carnitine Concentrationcontrasting
confidence: 99%
“…Carnitine is widely used in humans and monogastric animals but rarely in ruminants. Studies on rumen-protected L-carnitine in ruminants have only been reported by White (2002), Walker (2005), Solhjoo (2014) and Olagaray (2018), but all of them were related to plasma metabolism and growth performance, and there were no related reports on antioxidant status and cytokine abundance.…”
mentioning
confidence: 99%
“…Plasma samples were analyzed for free l ‐Carnitine concentration by the method of Xia and Folkers (1991) with modifications described by Walker et al. (2005).…”
Section: Methodsmentioning
confidence: 99%
“…Absence of additional bioavailability with RPC was also observed by White et al (2002); feedlot lambs supplemented with either RPC (20% l-carnitine) or unprotected carnitine (50% l-carnitine) fed at equal l-carnitine concentrations in the diet had similar increases in plasma carnitine concentrations. Rumenprotected carnitine fed to lambs at doses ranging from 0.25 to 10 g/d increased plasma carnitine concentrations relative to control, but no dose effect was present (Walker et al, 2005). Similar effects of crystalline and RPC observed across studies could potentially be due to hindered release of l-carnitine from protective coatings, affecting its intestinal absorption.…”
mentioning
confidence: 73%